Empirical evidence on factors shaping the savings rate of Polish households - Rószkiewicz, Małgorzata (Czynniki warunkujące zmienność stopy oszczędzania polskich gospodarstw domowych w świetle badań empirycznych, 2015)
The paper aimed at identifying the effects of the coincidence of socio-economic status and the advancement of the family life cycle on the savings rate. The multilevel regression model for data from empirical surveys was used. The obtained results allow us to explain how the differentiation of the saving rate that causes a poor fit of LCH models to the observed reality occurs. Ascribed to this differentiation is the explanation that allows us to reduce the area of unpredictability of the savings rate. These results show that the social representations of saving characteristic for various socio-economic groups are crucial factors that explain the variability of the savings rate, moderating its sensitivity to the demographic factors as defined in the economic theory. Moderation leads to two different tendencies. The first occurs among the households of a relatively low status and lies in the extension of consumption along with age, and it is stronger the lower the status of the household head is. The second, completely reverse, is present among households of a relatively high social status. The contraction of the time horizon of consumption manifests among these households, and it is stronger the higher the socio-economic status of a household head is.
Ekonometria = Econometrics, 2015, Nr 4 (50), s. 159-169
Keywords: LCH; multilevel regression model; multivariate correspondence analysis; social representation of saving; savings rate; wielopoziomowy model regresji; wielowymiarowa analiza korespondencji; społeczne reprezentacje oszczędzania; stopa oszczędzania